2001
DOI: 10.3346/jkms.2001.16.5.619
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Human Papillomavirus DNA in Nongenital Seborrheic Keratosis

Abstract: Absence of Human Papillomavirus DNA in Nongenital Seborrheic KeratosisSeborrheic keratosis (SK) is a benign epidermal tumor of unknown etiology. Because of its wart-like morphology, human papillomavirus (HPV) has been suggested as a possible causative agent. Viral involvement, however, has not been confirmed yet despite extensive research. The aim of this study was to evaluate the presence of HPV 6/11, 31, 33 DNA in nongenital SK. We analyzed 40 biopsy specimens taken from patients with nongenital SK using in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
2
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 18 publications
2
25
2
3
Order By: Relevance
“…This however is in disagreement with previous studies in which they described the etiology of SK as unknown,[17–20] but it is in agreement with Haw et al . [21] This study was the only research on UVB as a causative agent in inducing SK.…”
Section: Discussioncontrasting
confidence: 69%
“…This however is in disagreement with previous studies in which they described the etiology of SK as unknown,[17–20] but it is in agreement with Haw et al . [21] This study was the only research on UVB as a causative agent in inducing SK.…”
Section: Discussioncontrasting
confidence: 69%
“…This result is similar to the results of the following studies, which reported the absence of HPVs genome: Lee et al ., reported that HPV types 6/11, 31, and 33 were not found in non-genital SK. [8] Also, 28 (96%) cases of non-genital SK did not contain HPVs DNA sequences in Zhu's study. [9] It is interesting to note that HPVs detection by IHC in all of the 31 inverted follicular keratoses (IFK) samples performed by Asadi-Amoli revealed negative result.…”
Section: Discussionmentioning
confidence: 90%
“…Some EV-associated HPVs have been suggested to be associated with a diverse range of skin malignancies and premalignant diseases, 1,2 especially in immunocompromised patients. 3 According to their phylogenetic similarity, EV-associated HPVs consist of HPV 5,8,9,12,14,15,17,[19][20][21][22][23][24][25][36][37][38]47 and 49. 4 Using highly sensitive polymerase chain reaction (PCR), several unknown types belonging or related to EV-associated HPVs have been reported in renal transplant recipients (RTRs).…”
mentioning
confidence: 99%